Inovasi Mie Subtitut Tepung Oat dengan Cumi Bumbu Base genep - Saan, Daffirell Mursad; Taufiq, Riza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Bali is a city famous for its culinary delights. Bali has a variety of traditional foods rich in spices. Genep base is one of the traditional Balinese spices that has not been lost over time. Genep base has been available since 2000 years ago according to the lontar book. The author conducted research with the aim of finding out the combination of base genep products with noodles. This innovation of noodles substituting oat flour with squid base genep spices provides a traditional touch and unique taste. So far the author has not found research on the innovation of noodles substituted for oat flour with squid base genep seasoning, therefore the author brought up this innovation. The method used was organoleptic by carrying out 2 recipe formulation trials and data collection was carried out by distributing questionnaires to random panelists. The best result was Genep base noodles. 4.2 on a scale of 5 (very tasty), color 4.4 on a scale of 5 (very attractive), texture 4.6 on a scale of 5 (very soft), physical appearance 4.8 on a scale of 5 (very attractive). The results of this trial can be concluded that this innovative product of oat flour substitute noodles with squid base genep seasoning can be well received by the public.